Peran Corporate Social Responsibility Program Indofood Riset Nugraha Dalam Membentuk Brand Differentation - Alfareji Febrian Hanom; Muhamad Firzan Akbar; Putri Vania Iftatunnisa; Bintang Awal Ramadhan; Winda Dwi Astuti Zebua (STIKes Ibnu Sina Ajibarang, 2024)
This research discusses the role of PT. Indofood Tbk and PT. Indofood CBP Sukses Makmur Tbk in shaping brand differentiation through Corporate Social Responsibility (CSR) programs, with a focus on the Indofood Research Nugraha (IRN) initiative. The IRN program provides research funding to students to support research in the field of food, while the companies use various media to communicate their CSR initiatives. The research method employed is qualitative with descriptive analysis. Findings highlight the contributions of CSR programs in strengthening the company's image as an entity that cares about society and the environment, and creating brand differentiation that integrates social responsibility. By making CSR an integral part of the company's vision and mission, CSR becomes the foundation for all company activities, playing a crucial role in building a positive brand image and enhancing community engagement.